Novos espaços da política: a dinâmica das lutas locais - Santos, José Roberto dos (2011)
The dynamics of social fights in Santa Maria district, Aracaju, represents, in this study, the search process for understanding and analyzing the articulations of the social movements, their victories, and their ways of practicing politics, it proposes, therefore, a search for explanations and to reflect upon some issues such as: what are the dynamics of social fights and victories of the popular social movements is Santa Maria District? How do they work to solve their problems and to answer the demands along with the institutions that are responsible for the public policies in the district? With the answers to these and other questions, an analysis of the population‟s fights with the support of local social movements will be conducted. It will be done based on the historical-critical perspective of the social movements within the context of social live, through a qualitative approach based on semi=structured interviews applied to people who are close observers of the district‟s reality, and on the analysis of News contents that were published in two newspapers from Aracaju in previous years, especially from 2004 to 2008. In face of the material studied about the News from newspapers and the contents of magazines, it is evident that the local popular movements began as a new way of practicing politics that was characterized by a reproductive practice of the status quo. There is one perspective left for the population from Santa Maria District, that they demand the local leadership to take actions in face of their dynamic of fights